ANALISIS IMPLEMENTASI KEBIJAKAN PEMBATASAN LALU LINTAS DENGAN SISTEM GANJIL GENAP DI PROVINSI DKI JAKARTA - Fathya Ammaliasari, Puspita; Santoso, R. Slamet; Subowo, Ari (Journal of Public Policy and Management Review, 2024)
Congestion is the main traffic problem that occurs in DKI Jakarta Province. The DKI Jakarta Provincial Government together with the Department of Transportation (DISHUB) then implemented a traffic restriction policy using an odd-even system as an effort to deal with congestion problems in DKI Jakarta. This policy is a restriction on the use of four-wheeled vehicles according to vehicle plate numbers with the aim of reducing vehicle volume to overcome traffic jams. The aim of this research is to find out how the traffic restriction policy with an odd-even system is implemented in DKI Jakarta Province and to find out the supporting and inhibiting factors in policy implementation. The research method used is descriptive qualitative with data collection through observation, interviews, documentation, and literature study. The theory used is Merilee S. Grindle's Implementation Theory that consists of Content of Policy and Context of Implementation. The results of the research show that the implementers have carried out their duties well but still encounter obstacles such as an increase in vehicle volume and congestion on road sections where the odd-even policy is implemented. Supporting factors for policy implementation are good coordination between stakeholders, policy socialization, and good understanding from implementing officials, while inhibiting factors are lack of public awareness and resources in carrying out implementation.